2009
DOI: 10.1103/physrevlett.103.043001
|View full text |Cite
|
Sign up to set email alerts
|

Two-Source Double-Slit Interference in Angle-Resolved High-Energy Above-Threshold Ionization Spectra of Diatoms

Abstract: When an electron from a diatomic molecule undergoes tunneling-rescattering ionization, a novel form of destructive interference can be realized that involves all four geometric orbits that are available to the electron when it is freed, because both ionization and rescattering may take place at the same or at different centers. We find experimentally and confirm theoretically that in orientation-averaged angle-resolved high-order above-threshold ionization spectra the corresponding destructive interference is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…During the last years, electron interference effects have been widely investigated in electron-and ion-induced ionization [7][8][9][10][11][12][13][14][15][16][17][18], as well as in photoionization [19][20][21][22][23][24][25][26][27] of isolated atoms and molecules. In the electron interference experiments [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23], each single electron hits the position-sensitive detector like a particle but traverses the interferometer slits (or scatters on atomic centers) like a wave. Thus, over many repetitions, an interference pattern builds up as oscillations of the intensity I(θ d ) = (dI/dλ)dλ with the observation angle θ d [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, electron interference effects have been widely investigated in electron-and ion-induced ionization [7][8][9][10][11][12][13][14][15][16][17][18], as well as in photoionization [19][20][21][22][23][24][25][26][27] of isolated atoms and molecules. In the electron interference experiments [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23], each single electron hits the position-sensitive detector like a particle but traverses the interferometer slits (or scatters on atomic centers) like a wave. Thus, over many repetitions, an interference pattern builds up as oscillations of the intensity I(θ d ) = (dI/dλ)dλ with the observation angle θ d [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, a substantial experimental effort has been devoted to investigate these two-center interferences in the simplest diatomic molecules, mainly in the context of photoionization [see, e.g., (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)], but also in ionizing collisions with fast ions (18)(19)(20)(21) and electrons (22)(23)(24). However, due to the rapid decrease of σ 0 with photoelectron energy, i.e., with k e , the oscillations are usually hidden and must be uncovered through dividing the total cross section by an independent but arbitrary estimate of σ 0 , leading to equivocal interpretations (18,19).…”
mentioning
confidence: 99%
“…Dramatically different behavior was found between N 2 (σ g ) and O 2 (π g ) at parallel and perpendicular molecular orientation. This is crucial for explanation of the two--source double-slit destructive interference effect, which has been observed in experiments with randomly oriented O 2 molecules [10].…”
Section: Discussionmentioning
confidence: 99%
“…By θ L we define angle between the laser polarization vector and internuclear axis, while θ accounts for the angle between final momentum of the detected electron and internuclear axis. This novel two-source two-rescattering-centers interference has been observed in experiments with unaligned molecules [9,10]. Recently, we have shown that for elliptical polarization interference condition (5) still holds [11] but one should have in mind that k st is a complex solution of the saddle-point equations [12,13].…”
Section: General Theorymentioning
confidence: 99%